2019
DOI: 10.2991/ijcis.d.190722.001
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Fuzzy Cognitive Map Based on Hesitant Fuzzy Sets for Modeling Risk Impact on Electric Power System

Abstract: Electric power industry has been undergoing enormous transformations. Therefore, it is necessary to improve the security of electric power system and the decision capacity in the emergency process. As a complicated system, electric power system is affected by many factors, the reasoning of which can be regarded as a process that combines intuition and cognition. Uncertainty characterizes human cognitive and reasoning processes. Several extensions of fuzzy cognitive map (FCM) model have been suggested to handle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Yousefi S (with 9 papers) and Rezaee MJ (with 7 papers) have been among the most productive researchers in the field since 2017. Papageorgiou EI and Salmeron JL have 7 and 4 [79,116,73,144,145,74,132,11,98,159,115,164,124,143], Rezaee et al (2018b), [21], [86], [127], [102] 19…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yousefi S (with 9 papers) and Rezaee MJ (with 7 papers) have been among the most productive researchers in the field since 2017. Papageorgiou EI and Salmeron JL have 7 and 4 [79,116,73,144,145,74,132,11,98,159,115,164,124,143], Rezaee et al (2018b), [21], [86], [127], [102] 19…”
Section: Resultsmentioning
confidence: 99%
“…After that, they modeled the maintenance error-caused relationship and analyzed the failures using FCM. Khanzadi et al [70] modeled the causes of change orders in construction projects and analyzed them [86] presented a new version of the FCM based on the hesitant fuzzy sets called hesitant fuzzy cognitive maps (HFCMs). They aimed to model and analyze the impact of risks on the security of the electric power system by considering the intrapersonal hesitancy and the interpersonal hesitancy simultaneously.…”
Section: Hybridmentioning
confidence: 99%
“…Cheng [32] recommended a novel autocratic approach using group recommendations for HFSs to deal with the green hotel assessment problems. Liu et al [33] initiated the hesitant fuzzy cognitive maps and showed how to use it to explore the risk factors that arise in an electric power system. With the implementation of the HF-Complex Proportional Assessment (HF-COPRAS) method, Mishra et al [34] assessed and presented the ranking order of the service quality alternatives for vehicle insurance companies.…”
Section: Hesitant Fuzzy Set (Hfs)mentioning
confidence: 99%
“…Based on fuzzy and rough set theory, Renigier-Biłozor, Janowski, and d'Amato (2019) proposed an automated valuation model for real estate market. In these methods, the decision-making process tends to be uncertain and ambiguous as it involves complexity of human cognitive thinking (Liu et al, 2019a(Liu et al, , 2019bZeng, Peng, Bale zentis, & Streimikiene, 2019). Therefore, it is hard for decision-makers to provide precise assessments in the assessment process (Chi, Yeh, & Lai, 2011;Gao, 2018;Lu, Tang, Wei, Wei, & Wei, 2019).…”
Section: Introductionmentioning
confidence: 99%